Patient-Reported Outcome Measures in Atopic Dermatitis and Chronic Hand Eczema in Adults - Barrett, Amy; Hahn-Pedersen, Julie; Kragh, Nana; Evans, Emily; Gnanasakthy, Ari (The patient : patient-centered outcomes research, 2019)
Patient-reported outcome measures (PROMs) provide an important complement to physician-assessed clinical outcome measures in dermatologic diseases such as atopic dermatitis (AD) and chronic hand eczema (CHE). AD and CHE are chronic and relapsing inflammatory skin conditions that often co-occur. While both diseases result in various signs and symptoms that are burdensome and can negatively affect patients’ lives, there may be distinct differences in the signs, symptoms, burden, and health-related quality of life (HRQOL) impact of these diseases. The objective of this study was to identify and evaluate PROMs used in studies of AD and CHE. The aim was to explore the assessment of key symptoms and impacts, and identify any gaps in the measures in use. A structured review of the PubMed database was conducted to identify PROMs used or developed for use in AD or CHE. The Dermatology Life Quality Index (DLQI), the Pruritus/Itch Numeric Rating Scale (NRS), the Patient-Oriented Eczema Measure (POEM), and the Quality of Life in Hand Eczema Questionnaire (QOLHEQ) were identified and reviewed in detail. With these measures, the AD and CHE symptoms and impacts most commonly evaluated in the literature include dermatology-related HRQOL in the domains of symptoms and feelings, daily activities, leisure, work and school, personal relationships, and adverse effects; pruritus; sleep disturbance; AD-specific symptoms (dryness, itching, flaking, cracking, bleeding, and weeping/oozing); and CHE-specific symptoms (pain, itch, fissuring, redness, bleeding, and dryness). A review of regulatory labels of drugs approved for AD by the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) found that, among the four measures reviewed, the Pruritus NRS was included in the FDA and EMA labels for dupilumab, the DLQI was included in the EMA labels for dupilumab and tacrolimus, and the POEM was included in the EMA label for dupilumab. Key symptoms of AD (e.g. itching, flaking, cracking) and CHE (e.g. pain, itching, fissuring) are increasingly being assessed with PROMs; however, primary endpoints in clinical trials are often based on clinician-reported outcome measures. As therapeutic strategies in dermatology are targeted at specific dermatologic symptoms and diseases affecting specific sites (e.g. CHE), future research should explore patients’ experiences with these symptoms and sites and the changes with treatment that are most meaningful to them.